Characterization of insulin crystalline form in isolated β-cell secretory granules - Asai, Seiya; Moravcová, Jana; Žáková, Lenka; Selicharová, Irena; Hadravová, Romana; Brzozowski, Andrzej Marek; Nováček, Jiří; Jiráček, Jiří (Open biology, 2022)
Insulin is stored in vivo inside the pancreatic β-cell insulin secretory granules. In vitro studies have led to an assumption that high insulin and Zn2+ concentrations inside the pancreatic β-cell insulin secretory granules should promote insulin crystalline state in the form of Zn2+-stabilized hexamers. Electron microscopic images of thin sections of the pancreatic β-cells often show a dense, regular pattern core, suggesting the presence of insulin crystals. However, the structural features of the storage forms of insulin in native preparations of secretory granules are unknown, because of their small size, fragile character and difficult handling. We isolated and investigated the secretory granules from MIN6 cells under near-native conditions, using cryo-electron microscopic (Cryo-EM) techniques. The analysis of these data from multiple intra-granular crystals revealed two different rhomboidal crystal lattices. The minor lattice has unit cell parameters (a ≃ b ≃ 84.0 Å, c ≃ 35.2 Å), similar to in vitro crystallized human 4Zn2+-insulin hexamer, whereas the largely prevalent unit cell has more than double c-axis (a ≃ b ≃ c ≃ 96.5 Å) that probably corresponds to two or three insulin hexamers in the asymmetric unit. Our experimental data show that insulin can be present in pancreatic MIN6 cell granules in a microcrystalline form, probably consisting of 4Zn2+-hexamers of this hormone.
Keywords: insulin secretion; electron microscopy; subcellular vesicle; Langerhansovy ostrůvky; peptide hormone; beta-buňky; elektronová mikroskopie; Humans; secretory granules; Microscopy, Electron; lidé; Islets of Langerhans; Insulin; Insulin-Secreting Cells; crystallization in vivo; inzulin